You can go your own way: SNX-BAR coat complexes direct traffic at late endosomes. (June 2022) - Shortill, Shawn P.; Frier, Mia S.; Conibear, Elizabeth
Abstract: The endolysosomal network consists of highly dynamic membrane-bound compartments that control subcellular degradative and recycling processes. A conserved family of endosomal coat complexes known as SNX-BARs drive the formation of tubular membrane transport carriers for cargo retrieval. Whereas SNX1-related SNX-BARs were previously thought to rely on their association with the retromer complex to recognize cargo, recent work shows this class of SNX-BARs can directly bind and deliver cargo. In this review, we examine the retromer-independent roles of SNX-BAR proteins in yeast and metazoans and explore their functional overlap with endosomal sorting complexes and accessory factors. We also discuss new work that highlights the role of the disordered N-terminal regions of SNX-BARs in complex assembly and function.